On film editing an introduction to the art of film construction - Dmytryk, Edward 1908-1999 (Edward Dmytryk - on filmmaking, 2018)
In On Film Editing, director Edward Dmytryk explains, in clear and engaging terms, the principles of film editing. Using examples and anecdotes from almost five decades in the film industry, Dmytrykoffers a masterclass in film and video editing. Written in an informal, "how-to-do-it" style, Dmytryk shares his expertise and experience in film editing in a precise and philosophical way, contending that all parties on the film crew-from the camera assistant to the producer and director-must understand film editing to produce a truly polished work. Originally published in 1984, this reissue of Dmytryk's classic editing book includes a new critical introduction by Andrew Lund, as well as chapter lessons, discussion questions, andexercises